Force dysmetria in spinocerebellar ataxia 6 correlates with functional capacity - Casamento Moran, Agostina; Chen, Yen-Ting; Kwon, MinHyuk; Snyder, Amy; Subramony, S H; Vaillancourt, David; Christou, Evangelos A. (Frontiers in Human Neuroscience, 2015)
Spinocerebellar ataxia type 6 (SCA6) is a genetic disease that causes pure cerebellar degeneration affecting walking, balance, and coordination. One of the main symptoms of SCA6 is dysmetria. The magnitude of dysmetria and its relation to functional capacity in SCA6 has not been studied. Our purpose was to quantify dysmetria and determine the relation between dysmetria and functional capacity in SCA6. Ten individuals diagnosed and genetically confirmed with SCA6 (63.7 ± 7.02yrs) and nine age-matched healthy controls (65.9 ± 8.5yrs) performed goal-directed isometric contractions with the ankle joint. Dysmetria was quantified as the force and time error during goal-directed contractions. SCA6 functional capacity was determined by ICARS and SARA clinical assessments. We found that SCA6 participants exhibited greater force dysmetria than healthy controls (P < 0.05), and reduced time dysmetria than healthy controls (P < 0.05). Only force dysmetria was significantly related to SCA6 functional capacity, as measured with ICARS kinetic score (R2 = 0.63), ICARS total score (R2 = 0.43), and SARA total score (R2 = 0.46). Our findings demonstrate that SCA6 exhibit force dysmetria and that force dysmetria is associated to SCA6 functional capacity. Quantifying force and time dysmetria in individuals with SCA6 could provide a more objective evaluation of the functional capacity and disease state in SCA6.